Too Much Choice and Consumer Decision Making: The Moderating Role of Consumer Involvement - Kamran Khan; Syed Karamatullah Hussainy; Irfan Hameed; Kashif Riaz (JISR Management and Social Sciences & Economics, 2021)
The study attempts to explore the choice available for grocery consumers and its impact on decision-making. The study’s design includes the consumer’s personal involvement towards the purchase, the emotions, and subsequent satisfaction. For a moderated-mediation model,  the data set of 401 respondents were finalized to test the measurement and structural models.  The research has established that it is not necessary that consumers are always happy when  they have more choices available. Further, it was also established that involvement has a role  to play in the emotions which lead to purchasing intentions. The involvement perspective in  the model makes this study unique because the part of consumer involvement as a moderator  to choices and emotions has not been studied before extensively. The manufacturers must  determine the array of choices because producing variety does not always generate more  revenues in this part of the world. The study opens new avenues for the researchers to dig into  the details and identify consumer behaviors when various choices for consumers are available.